The new encyclopedia britnannica in 30 volume, macropedia Volume 4 / William Benton - Benton, William (2001)
Colonization and the spread of Buddhism, the classical age, political changes, economic changes, the Portuguese in Ceylon, Buddhism and society, Dutch rule in Ceylon, the British in Ceylon , constitutionalism and nationalism, murals other works, historical development, structural elements, repertories, general features.